Action Plan for the Provision of Vitamins and Minerals to the Tanzanian Population through the Enrichment of Staple Foods - World Bank (Washington, DC, 2013)
The United Republic of Tanzania has a severe vitamin and mineral deficiency problem. Every year deficiencies in iron, vitamin A and folic acid cost the country over US$ 518 million, around 2.65 % of the country's GDP. Beyond the economic losses, vitamin and mineral deficiencies are a significant contributor to infant mortality, with over 27,000 infant and 1,600 maternal deaths annually attributable to this cause.2 In fact, if all of these deaths could be avoided, the infant mortality rate (IMR) in Tanzania could be reduced to 41.5 per 1,000 population, which would virtually ensure achievement of the MDG goal for IMR (40/1,000). To reduce this huge annual loss, an integrated national vitamin and mineral deficiency control programme is needed which is embedded in the national nutrition policy. Food fortification or enrichment should be an integral but not the only part of such a programme.